PENGARUH LINGKUNGAN TOKO DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PELANGGAN PADA PT. MATAHARI PUTRA PRIMA, Tbk HYPERMART SUN PLAZA MEDAN - Ruth Felicia Angelika Pasaribu; Rio Imelda Simbolon; Herni Safira Setiadi; Wirta Lestari Gea (Lembaga Penelitian dan Pengabdian Kepada Masyarakat-Universitas Darma Agung. (LPPM_UDA), 2021)
The purpose of the study was to examine and analyze the influence of the store environment and promotion on purchasing decisions at PT. Matahari Putra Prima, Tbk (Hypermart) Sun Plaza Medan. The researcher conducted the research at PT. Matahari Putra Prima, Tbk (Hypermart) Sun Plaza Medan, located at Jalan KH. Zainul Arifin No. 7 Medan Polonia. The researcher planned the research activities in April 2019 - September 2019. The approach of this research was quantitative research. The type of the research was quantitative descriptive research. The nature of this research was descriptive explanatory research. The population in this study was some customers of PT. Matahari Putra Prima, Tbk (Hypermart) Sun Plaza Medan, as many as 1000 customers. The population in this study was some customers who made purchases at PT. Matahari Putra Prima, Tbk (Hypermart) Sun Plaza Medan, amounting to 1000 customers, where for testing validity and reliability used by researchers, there were 30 customers and the rest were 286 customers as sample test. Before the regression model obtained was used to test the hypothesis, first the model was tested in the classical assumption. The classical assumption test used included: normality test, multicollinearity test, and heteroscedestity test. This data analysis model applied multiple regression analysis. The results of the study at the same time became the conclusion of the study was a shop environment of 3.048 with a significant value of 0.003 partially had significant effect on purchasing decisions at PT. Matahari Putra Prima, Tbk (Hypermart) Sun Plaza Medan. Promotion amounting to 4.037 with a significant value of 0,000 partially had significant effect on purchasing decisions at PT. Matahari Putra Prima, Tbk (Hypermart) Sun Plaza Medan.